l-Threonine Export: Use of Peptides To Identify a New Translocator from Corynebacterium glutamicum - Simic, Petra (American Society for Microbiology, 2001)
Bacterial mechanisms for the uptake of peptides and their hydrolysis to amino acids are known in great detail, whereas much less is known about the fates of the peptide-derived amino acids. We show that the addition of l-threonine-containing di- or tripeptides results in reduction of the growth of Corynebacterium glutamicum, with concomitant high intracellular accumulation of l-threonine to up to 130 mM. Using transposon mutagenesis and isolation of mutants with increased Thr peptide sensitivity, nine open reading frames (ORFs) were identified, almost all encoding hypothetical proteins of unknown function. Three ORFs encode membrane proteins. Their individual functional characterizations in the wild-type background led to the identification of thrE. Upon thrE overexpression, growth is no longer sensitive to the presence of the Thr peptide, and l-threonine is exported at a rate of 3.8 nmol min(−1) mg of dry weight(−1), whereas the rate of export of a thrE inactivation mutant is reduced to 1.1 nmol min(−1) mg of dry weight(−1). In addition to l-threonine, l-serine is also a substrate for the exporter. The exporter exhibits nine predicted transmembrane-spanning helices with long charged C and N termini and with an amphipathic helix present within the N terminus. All these data suggest that the carrier encoded by thrE serves to export small molecules such as l-threonine and that the carrier is a prototype of a new translocator family. Homologues of ThrE are present in Mycobacterium tuberculosis and Streptomyces coelicolor.